Interpretation of the Norms of Criminal Jurisdiction Objects under the Hong Kong National Security Law - Meng, Weitao (International Journal of Social Sciences and Public Administration, 2024)
The Hong Kong National Security Law specifies the specific targets of sanctions, and the legislative content of the law on criminal jurisdiction objects clarifies the scope of behaviors protected and prohibited by law. Chapter 3 of the Hong Kong National Security Law specifies four types of crimes that endanger national security, including the crimes of secession, subversion of state power, terrorist activities, and collusion with foreign or overseas forces to endanger national security. From the perspective of legal interpretation, by grasping the dual elements of criminal intent and criminal behavior, the specific composition of the criminal jurisdiction objects stipulated in the law is clarified, revealing the particularity and strictness of the Hong Kong National Security Law in safeguarding national security. The normative interpretation of the specific criminal jurisdiction objects of this law can clearly stipulate the constituent elements of specific criminal acts, provide strong guidance for the effective jurisdiction of crimes that endanger national security in the Hong Kong Special Administrative Region, strengthen the prevention and crackdown on acts that endanger national security, and effectively safeguard national sovereignty, security, and development interests.